Capronate use of 17-hydroxy-19-norprogesterone as injectable contraceptive depot. - Hurtado, Hilario (2015)
The authors have studied the contraceptive effect of 17-Alpha Hydroxi-19-Norprogesterona Capronate (SN - 582) in 21 normal women; the effect is present during 6-8 weeks after the inyection of 200 mg. During this time menstrual irregularities as spotting and amenorrhea were observed, but their incidence was lower than those produced by the norethisterone enanthate (SN - 393).